ANALISIS EKONOMI RUMAH TANGGA NELAYAN DI SEKITAR KAWASAN HUTAN MANGROVE DESA KUALA SELAT KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Yurizal, Wenda; Iyan, Rita Yani; Ekwarso, Hendro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Every household wants to fulfill daily needs but for fishermen households often these needs can not be fulfilled by relying on basic work, efforts to increase income, among others, can be pursued through the productivity effort of all fishermen family resources. The purpose of this research is to know and describe the economic condition of fisherman households based on income and expenditure around Mangrove Forest area in Kuala Selat Village, Kateman Subdistrict, Indragiri Hilir Regency. The population in this study is the people who live in the mangrove forest area that works as a fisherman of 276 families. This research uses purposive sampling technique in determining the sample of research, so get 55 KK as research sample. Data taken from the respondents using questionnaires. The method of analysis used in this research is descriptive analysis. The results of this study indicate that the income of fishermen households in the mangrove forest area of Kuala Selat Village is Rp. 1,500,000 to Rp. 2,500,000. this study shows that income in fishermen households is still relatively low. The expenditure of fisherman households in the mangrove forest area of Kuala Selat Village is Rp. 1,210,000 to Rp. 1.870 million. This study shows that household expenditures in fishermen are still classified according to the income they earn. The Local Government of Indragiri Hilir Regency is expected to give more attention to the mangrove forest because it can affect the economy of the people whose livelihood as fisherman, so it can increase the amount of fisherman's income every month.